TRADITIONAL SILK HEADSCARVES "TASTAR" OF THE KUMYKS (TO THE PROBLEM OF THE REVIVAL OF THE TRADITIONAL CRAFT) - Amirhanova, Aida Kiasbekovna (History, Archeology and Ethnography of the Caucasus, 2022)
The silk headscarves tastars were widespread in the North Caucasus in the late 19th century. In Dagestan, they were produced in the Kumyk villages and were part of the traditional costume of the Kumyk women. The aim of the article is to consider the modern state of traditional crafts among the peoples of Dagestan on the example of the tastar headscarves, to demonstrate the relevance of revival of some types of national artistic crafts. The exclusion of applied arts by industrial products, globalization and the elimination of ethnic and cultural differences caused by it, actualized the study of pieces of material culture in the scientific and art community in order to preserve them. In Dagestan, the preservation of ancient folk crafts is implemented through various educational programs, the creation of centers of traditional culture, schools of folk arts. The article is based on the study, conducted by the methods of interview and participant observation in such centers. The author visited several functioning centers of teaching tastar weaving in Dagestan (Nizhnee Kazanishe, Aksay), talked with craftswomen. The article provides versions of origin of this unique technique of tastar weaving, traces the history of this craft, describes active centers, gives names of the keepers of the old tradition. The conducted research reveals that the modern state of tastar weaving is mainly supported by enthusiasts in villages – old centers of the studied craft.
Keywords: trades; crafts; revival; the peoples of Dagestan; patriotic education; heritage; historical memory.